The Banners In The Central Maghreb Through Portulan Charts - 8th Hijri Century/ 14th Century Ad – (Journal of Namibian Studies : History Politics Culture, 2024)
The banners are a difficult topic to address in scientific research due to the lack of material archaeological sources and evidences. In this regard, what has been found does not satisfy a researcher's passion for a comprehensive study of flags and banners of all kinds. One of these few archaeological evidences is known as Portulan charts (nautical charts). In this paper, we will highlight the flags and banners of the Central Maghreb, which were drawn on these charts, mainly in the first phase that witnessed the manufacture and development of Portulan charts in the 8th CenturyHijri, 14thcentury AD.